Strategic insights from senior management in implementing digital transformation in Vietnamese SMEs - Trang, Do Thi My; Son, Nguyen Duc; Thanh, Tran Ha; Hung, Dinh Viet (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to explore senior management perceptions of digital transformation (DX) within Vietnamese small and medium-sized enterprises (SMEs). It seeks to evaluate the impact of these perceptions on the successful implementation of DX initiatives and provide strategic recommendations for aligning these initiatives with organizational goals. A qualitative approach was used, conducting semi-structured interviews with senior managers from various Vietnamese SMEs to gain insights into their DX experiences and challenges. While DX is crucial for maintaining competitiveness, its adoption necessitates extensive cultural, structural, and operational transformations. SME leaders are cautious about financial and operational risks and favor a phased, context-sensitive approach. Senior management perceptions are crucial for DX success. Effective adoption demands adaptive leadership, cultural shifts, and a gradual, strategic implementation to address SME-specific challenges. The study provides practical recommendations for SMEs in Vietnam, emphasizing leadership adaptability, cultural alignment, and phased DX implementation for sustainable growth and success.